PENAFSIRAN KITAB UNDANG-UNDANG HUKUM PIDANA TENTANG PENCURIAN DALAM KELUARGA TERHADAP PERKAWINAN DI BAWAH TANGAN PADA PUTUSAN PENGADILAN NEGERI TELUK KUANTAN NOMOR 1/PID.B/2020/PN TLK - Atika Shalwani; Erdianto Erdianto; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Theft in the family as stipulated in Article 367 of the Criminal Code, the legislator stipulates theft as a criminal complaint (klacht delict), i.e. theft that can only be prosecuted on the basis of complaint from the aggrieved party. The type of complaint contained in the Criminal Code is a relative complaint, namely a complaint against the person who committed the theft and the absolute complaint that is his or her actions. Regarding theft in the family stipulated in Article 367 of the Penal Code, neither husband nor wife can sue each other in the event of theft between the two parties, the legal principle of marital property is that by marrying the husband and wife, then all the assets brought by the husband and wife into the marriage, enter into a group of property, called the property of unity. But based on this case, the wife has suffered losses for her husband's actions. However, the wife cannot sue her husband in positive legal rules. Plus their marital status is marriage under hand. So it is not recognized by the State and the wife is difficult to get justice for.The purpose of this research is to find out how the legal process against theft in the marital family is under hand, as well as the known interpretation of Article 367 of the Criminal Code against the case of theft in marriage under hand. This research will be compiled using a type of normative juridical research, namely research focused on examining the application of rules or norms in positive hokum. The approach used in this study is to use a normative approach that is literature law research.The result of the study conducted by the authors is that, although a delik is a complaint in this case in the form of a criminal theft in the family to conduct an investigation of the relic, it is known that the judge ruled in the case of theft in the marriage family under the hands is thus only included in the 362 Criminal Code because it fulfills the element of taking something, which is entirely or partially belonging to another person , with the intent to be unlawfully owned.Keywords: Interpretation – Marriage under Hand – Theft